Pengaruh Gender Diversity dan Age Diversity terhadap Financial Performance dalam Institusi Perbankan Yang Terdaftar di Bursa Efek Indonesia - Nuraeni, Nuraeni; Hakim, Luqman; Nurdin, M. Arief Firman; Kinasih, Dini Hadiati Putri (Dinasti Research, 2025)
This study investigates the effect of gender diversity and age diversity on the financial performance of banking companies listed on the Indonesia Stock Exchange. The aim of this research is to determine whether gender and age diversity on the board have an influence on decision-making that affects the company's financial performance. This is an associative-quantitative study using multiple regression analysis, with data processed using the EViews program. The results of the study show that gender diversity and age diversity of the board have an insignificant effect on the financial performance of banking companies listed on the Indonesia Stock Exchange.